Pacific Fono: a community-based initiative to improve rheumatic fever service delivery for Pacific Peoples in South Auckland - Rawiri McKree Jansen; Jadene Wheeler; Rachel Brown; Anneka Anderson; The National Hauora Coalition (CSIRO Publishing, 2020)
ABSTRACT BACKGROUND AND CONTEXTRheumatic fever inequitably affects Māori and Pacific children in New Zealand. School-based throat swabbing services, such as the South Auckland Mana Kidz programme, are a key element of rheumatic fever prevention interventions. ASSESSMENT OF THE PROBLEMCounties Manukau has the highest national rates of rheumatic fever (4.7 per 100,000 for first recorded rates). Given these disparities, Mana Kidz undertook an exploratory, community-based initiative to improve its service delivery for Pacific Peoples. RESULTSMana Kidz held a Pacific Leaders' Fono (meeting) to discuss initiatives to improve rheumatic fever outcomes in South Auckland focused around challenges and solutions for addressing rheumatic fever, effective engagement strategies and leadership qualities needed to drive initiatives. Oral and written responses from 66 attendees were collected and thematically analysed. Four key themes were identified around challenges and solutions for rheumatic fever: social determinants of health; cultural responsiveness; health system challenges; and education, promotion and literacy. Three effective engagement strategies were identified: by Pacific for Pacific; developing a rheumatic fever campaign; improving health services. Three key leadership attributes were identified: culturally responsive leaders; having specific expertise and skills; youth-driven leadership. STRATEGIES FOR IMPROVEMENTMana Kidz has now created Pacific leadership roles in rheumatic fever governance groups, promotes Pacific workforce development and endorses Pacific-led initiatives and partnerships. LESSONSRecognising the value of critical reflection and the importance of good governance and collaborative, right-based partnerships in health services.